Clinical manifestation of acute cerebral infarcts in multiple arterial territories. Issue 8 (1st August 2021) - Novotny, Vojtech; Aarli, Sander Johan; Netland Khanevski, Andrej; Bjerkreim, Anna Therese; Elnan Kvistad, Christopher; Fromm, Annette; Waje‐Andreassen, Ulrike; Naess, Halvor; Thomassen, Lars; Logallo, Nicola
Abstract: Objectives: We aimed to assess frequencies and radiological aspects of single‐ and multiterritory clinical manifestation among patients with acute cerebral infarcts in multiple arterial territories (MACI). Materials & methods: We retrospectively reviewed admission records and diffusion‐weighted magnetic resonance imaging of patients with MACI admitted to our stroke unit between 2006 and 2017. MACI was defined as acute cerebral ischemic lesions in at least two out of three arterial cerebral territories, that is, the left anterior, right anterior and the bilateral posterior territory. Patients with single‐ and multiterritory clinical manifestation were then compared for topographical distribution of the ischemic lesions, the number of ischemic lesions, and The Oxfordshire Community Stroke Project classification. Results: Out of 311 patients with MACI, 222 (71.4%) presented with single‐territory clinical manifestation. Involvement of the left hemisphere (OR = 0.37, 95% CI 0.16–0.82), less than five ischemic lesions (OR = 0.58, 95% CI 0.35–0.97), and partial anterior circulation infarct clinical stroke syndrome (OR = 0.57, 95% CI 0.34–0.97) were associated with single‐territory clinical manifestation. Involvement of all three territories (OR = 2.58, 95% = 1.48–4.50), more than 10 ischemic lesions (OR = 2.30, 95% CI 1.32–4.01) and total anterior circulation infarct clinical stroke syndrome (OR = 3.31, 95% CI 1.39–7.86) were associated with multiterritory clinical manifestation. Conclusion: Most patients with MACI present with single‐territory clinical manifestation on admission. Diffusion‐weighted magnetic resonance imaging is therefore necessary for a definite diagnosis. Abstract : We aimed to assess frequencies and radiological aspects of single‐ and multi‐territory clinical manifestation among patients with acute cerebral infarcts in multiple arterial territories (MACI). The results show that most patients with MACI present with single‐territory clinical manifestation on admission. Diffusion‐weighted magnetic resonance imaging is therefore necessary for definite diagnosis.